2020
DOI: 10.1111/jfpp.15063
|View full text |Cite
|
Sign up to set email alerts
|

Feed rate, water addition rate and mixture composition nexus role on alterations of nutritional properties in extrusion of composites containing rice ( Oryza sativa ), sorghum [ Sorghum bicolor ), and bamboo ( Yushania alpina ) shoots

Abstract: Extrusion cooking impacts positively on the nutritional status of a food when compared to their raw form. The objective of this study was to determine the effect of ingredient variables: Feed Rate, Water Addition Rate, and Mixture Composition on the extent of nutritional changes to rice flour enriched with sorghum (Sorghum bicolor) and bamboo (Yushania alpina) shoots on extrusion processing. A 5 × 3 × 2 factorial experimental set up for feed blending, water addition rate, and feed rate in single screw dry type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
5
0
0
Order By: Relevance
“…It has been mentioned that the short‐time processing by extrusion gives a potential advantage for maintaining phenolics as compared with other heating treatments (Sarka et al, 2020). The results were in accordance with that of Wafula et al (2020), where extrusion cooking had a positive effect on the nutritional properties of sorghum, rice, and bamboo composites. Similar effect of BT was observed by Bekele, Nosworthy, Tyler, and Henry (2021) for chickpea–sorghum blends (50:50).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It has been mentioned that the short‐time processing by extrusion gives a potential advantage for maintaining phenolics as compared with other heating treatments (Sarka et al, 2020). The results were in accordance with that of Wafula et al (2020), where extrusion cooking had a positive effect on the nutritional properties of sorghum, rice, and bamboo composites. Similar effect of BT was observed by Bekele, Nosworthy, Tyler, and Henry (2021) for chickpea–sorghum blends (50:50).…”
Section: Resultssupporting
confidence: 92%
“…T A B L E 3 Chemical properties of the sorghum-mung bean-based snacks. results were in accordance with that of Wafula et al (2020),…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 92%
“…It has been mentioned that the short‐time processing by extrusion gives a potential advantage for maintaining phenolics as compared to other heating treatments (Sarka et al, 2020). The results were in accordance with that of Wafula and Mahungu (2020), where extrusion cooking had a positive effect on the nutritional properties of sorghum, rice and bamboo composites. Similar effect of BT was observed by Bekele et al (2021) for chickpea–sorghum blends (50:50).…”
Section: Resultssupporting
confidence: 91%
“…Earlier published reports support the concept that as compared to other thermal treatments, short-span processing of samples through extrusion is beneficial as it will help to maintain phenolic compounds [48,49]. The findings in the present study are in agreement to reported observations by Wafula et al [50], which showed that cooking by extrusion has shown a modulating effect on quality attributes and nutrients of grains (rice and sorghum) and bamboo composites. Similarly, Bekele et al [46] has also reported comparable results for chickpea-sorghum blends (50 : 50).…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 93%